Irisin Suppresses Nicotine-Mediated Atherosclerosis by Attenuating Endothelial Cell Migration, Proliferation, Cell Cycle Arrest, and Cell Senescence - Chen, Junye; Li, Kang; Shao, Jiang; Lai, Zhichao; Gao, Ran; Wang, Chaonan; Song, Xitao; Guo, Wenjun; Yu, Xiaoxi; Du, Fenghe; Zhu, Zhan; Wang, Jiaxian; et al. (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerotic disease has become the major cause of death worldwide. Smoking, as a widespread independent risk factor, further strengthens the health burden of atherosclerosis. Irisin is a cytokine that increases after physical activity and shows an atheroprotective effect, while its specific mechanism in the process of atherosclerosis is little known. The reversal effect of irisin on intimal thickening induced by smoking-mediated atherosclerosis was identified in Apoe–/– mice through the integrin αVβ5 receptor. Endothelial cells treated with nicotine and irisin were further subjected to RNA-seq for further illustrating the potential mechanism of irisin in atherosclerosis, as well as the wound healing assays, CCK-8 assays, β-gal staining and cell cycle determination to confirm phenotypic alterations. Endothelial differential expressed gene enrichment showed focal adhesion for migration and proliferation, as well as the P53 signaling pathway for cell senescence and cell cycle control. Irisin exerts antagonistic effects on nicotine-mediated migration and proliferation via the integrin αVβ5/PI3K pathway. In addition, irisin inhibits nicotine-mediated endothelial senescence and cell cycle arrest in G0/G1 phase via P53/P21 pathway. This study further illustrates the molecular mechanism of irisin in atherosclerosis and stresses its potential as an anti-atherosclerotic therapy.